Balancing Risks and Benefits: Perioperative Management of Severe Pulmonary Stenosis in Noncardiac Surgery – A Case Study - Kelvin, Jerico; Utama Armyn, Andi Alief; Patimang, Yulius; Amir, Muzakkir; Mappangara, Idar; Qanitha, Andriany (Gaceta Médica de Caracas, 2024)
Background: Pulmonary stenosis accounts for 7 %-10 % of all congenital heart disease cases. Given their extended lifespans, these patients often require increased diagnostic, interventional, and surgical interventions for noncardiac conditions. This case report focuses on the perioperative evaluation of a patient diagnosed with severe pulmonary stenosis who was scheduled for non-cardiac surgery. Case Presentation: A 19-year-old girl was referred to the Cardiology Department for a preoperative assessment before undergoing Salpingo-Oophorectomy for an Ovarian Cystic Neoplasm. Since the age of 6, she has experienced limited exercise tolerance and exertional dyspnea.